Contribuição laboratorial para a diferenciação entre colonização e infecção por leveduras em pacientes hospitalizados - Vidigal, Pedrina Gonçalves (2009)
The beginning of 80s has been noticeable by hospital fungal infections, mainly in immunocompromised patients, resulting in serious health problems. Yeasts from Candida genera are among the most important agents from this scenario, and especially non-albicans species emerge not only as colonizers, but also as pathogens responsible by severe infections. The urinary tract (UT) and respiratory tract (RT) are anatomical sites colonized by these microorganisms, which are also susceptible to infections that could disseminate to bloodstream. Nowadays, yet there are some controversies about the medical action towards yeast laboratorial finding in urine or pulmonary samples, once these criteria utilized for mycoses diagnosis in these sites are still not clear and well established. The objective of this work was to compare the molecular profile of C. tropicalis isolated in samples from UT (urine and blood), and in RT (biopsy and endotracheal tube) as well, from hospitalized patients. Thus, the genomic DNA from these samples was sequenced, using oligonucleotides that amplified ITS regions. After that, the obtained sequences were submitted to data bank of NCBI, and alignment performed by using ClustalW2 software. Therefore, the results revealed that the samples from UT presented an identical genetic pattern between themselves, as well as the RT ones.